2020
DOI: 10.1186/s12905-020-00940-8
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal repaired cesarean section diverticulum is beneficial in women with two prior cesarean sections

Abstract: Background: The aim of this study was to evaluate the effect of vaginal repair in patients with cesarean section diverticulum (CSD) who had one or two previous cesarean sections (CSs). Methods: From January 2012 to December 2014, 248 women with CSD underwent vaginal repair surgery in Shanghai First Maternity and Infant Hospital. These included 193 women with one previous cesarean section and 55 women with two previous cesarean sections. Excision and suture of CSD was performed through a vaginal approach. The d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Because of the two-child policy, if the patient has undergone a first caesarean section, caesarean scar defect (CSD) and its long-term complications have recently captured the attention of more gynecologists. Patients with Isthmocele may face problems with infertility because accumulated blood can degrade the quality of sperm and cervical mucous [ 8 ]. Operative methods in symptomatic Isthmocele advocated include hysteroscopy, laparoscopy, and vaginal repair [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the two-child policy, if the patient has undergone a first caesarean section, caesarean scar defect (CSD) and its long-term complications have recently captured the attention of more gynecologists. Patients with Isthmocele may face problems with infertility because accumulated blood can degrade the quality of sperm and cervical mucous [ 8 ]. Operative methods in symptomatic Isthmocele advocated include hysteroscopy, laparoscopy, and vaginal repair [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Isthmocele may face problems with infertility because accumulated blood can degrade the quality of sperm and cervical mucous [ 8 ]. Operative methods in symptomatic Isthmocele advocated include hysteroscopy, laparoscopy, and vaginal repair [ 8 , 9 ]. Studies have indicated that amongst all surgical methods, vaginal repair for CSD is a minimally invasive procedure; it allows good exposure and accurate resection and repair of full-thickness myometrium [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two arguments for suturing methods in vaginal surgery. The first is a single‐layer 108 , 109 , 110 , 111 , 112 , 113 or double‐layer 65 , 80 , 114 , 115 , 116 , 117 , 118 closure. In the case of CS, the double‐layer procedure is superior to the single‐layer procedure in avoiding CSD.…”
Section: Vaginal Surgery In Women With Csdimentioning
confidence: 99%
“…[ 1 ] The vaginal CSD repair technique has been reported and commonly practiced in China and overseas. [ 2 3 4 5 6 ] Like Hoang and An Nguyen, we used the hysteroscopy to illuminate the site and visualize the uterine diverticulum directly because, technically, it may sometimes be difficult to locate the CSD. This vaginal repair and suturing of CSD are easier than laparoscopic surgery.…”
mentioning
confidence: 99%